Presepsin Levels and Neutrophil-to-Lymphocyte Ratio are Positively Correlated with Procalcitonin Levels in Early Onset Neonatal Sepsis - Ni Putu Sukma Sumantri Prabandari; Ni Kadek Mulyantari; Made Sukmawati; Anak Agung Ngurah Subawa; I Wayan Gede Artawan Eka Putra; Anak Agung Wiradewi Lestari; I Nyoman Wande; Ni Nyoman Mahartini (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Early-onset neonatal sepsis (EONS) is an acute infection and sepsis occurring within the first 24 hours of new-born life. An increase in procalcitonin levels, presepsin levels, and neutrophil-to-lymphocyte ratio (NLR) in EONS subjects have been reported. However, whether presepsin levels and NLR affect the procalcitonin levels in EONS patients who have received antibiotic therapy has not been certainly known. This study was conducted to determine the correlation between presepsin levels and NLR with procalcitonin levels in EONS subjects.METHODS: A cross-sectional study involving 52 EONS subjects were conducted, and blood samples from subjects were collected. Presepsin levels were examined by enzyme-linked immunosorbent assay (ELISA) method, NLR was calculated from the absolute number of neutrophils divided by the absolute number of lymphocytes, and procalcitonin levels were examined by chemiluminescent microparticle immunoassay (CMIA) method. RESULTS: Median of procalcitonin levels and presepsin levels were 0.435 (0.12-9.11) ng/mL and 108.33 (71.43-1287.76) ng/L, respectively. While NLR value was 1.68 (0.2-7.52). There was significant difference between procalcitonin and presepsin levels (p=0.000), and so does between procalcitonin levels and NLR (p=0.001). Based on the multivariate analysis, presepsin levels also affected the procalcitonin levels (p=0.000; 95% CI: 0.001-0.004).CONCLUSION: The results of the study showed that there was significant correlation between presepsin levels and NLR with procalcitonin levels in EONS patients, suggesting that presepsin levels, NLR, and procalcitonin levels are potential candidates for EONS biomarkers.KEYWORDS: EONS, NLR, presepsin, procalcitonin